Translocality, Remittances, and Food Security in the Ghana-Qatar Migration Corridor - Bernard Owusu; Jonathan Crush (African Human Mobility Review)
This paper examines the impact of migrant remittances on household food security in the Ghana-Qatar migration corridor. Drawing on a 2023 survey of migrant-sending households in Ghana and in-depth qualitative interviews with migrants in Qatar, the study explores the characteristics, determinants, and patterns of remitting. The findings reveal that cash remittances play a crucial role in enhancing food security and the overall welfare of households in Ghana. However, the pressure to remit affects the food security of migrants in Qatar significantly, and they often adopt various coping strategies to manage their limited resources. The paper highlights the translocal nature of Ghanaian households, where remittances contribute to the cultural and economic sustenance of families. The study underscores the dual role of remittances in supporting household food security while imposing financial constraints on migrants and calls for policies that address the needs of both remitters and recipients.